Landscape and power in early China: The crisis and fall of the Western Zhou, 1045-771 BC - Feng, Li (Cambridge University, 2013)
The ascendancy of the Western Zhou in Bronze Age China, 1045-771 B.C., was a critical period in the development of Chinese civilization and culture. This book addresses the complex relationship between geography and political power in the context of the crisis and fall of the Western Zhou state. Drawing on the latest archaeological discoveries, the book shows how inscribed bronze vessels can be used to reveal changes in the political space of the period, and explores literary and geographical evidence to produce a coherent understanding of the Bronze Age past.